Arabic language learning trajectories: a narrative analysis of identity formation among thai students - Ahmad Maghfurin (Lentera Negeri, 2026)
This study takes as its core research subject the Arabic language learning trajectories of Thai international students enrolled at the State Islamic University of Walisongo Semarang, Indonesia. This study is designed with a qualitative research orientation, adopting the narrative inquiry method. Data collection combines documentary analysis and unstructured in-depth interviews. For the analysis stage, this study applies the interactive analysis model proposed by Miles and Huberman. This study maps out a four-stage interconnected trajectory of the international students’ Arabic language learning: academic cultural adaptation, language proficiency advancement, competency certification, and the formation of a hybrid academic identity. It also identifies three types of inherent challenges the students face, stemming from differences in educational backgrounds, language foundations, and teaching traditions. In response, the students have developed four corresponding adaptive strategies: interacting with instructors, collaborating with peers, engaging in self-directed learning, and utilizing digital resources. This study further finds that Arabic language competency certification can be converted into three forms of capital: intellectual capital, spiritual capital, and social capital. These capitals support three core competencies of the international students: participation in Islamic academic activities, cross-cultural communication, and resilience in transnational academic environments. The core argument of this study is that Arabic language learning is far from a simple acquisition of linguistic competence, but rather a complex process of identity negotiation.